ANALISIS KEMAMPUAN LAHAN MANGROVE KOTA SURABAYA DENGAN SISTEM INFORMASI GEOGRAFIS - Faisal Fakhruddin; Maroeto; Purnomo Edi Sasongko (BPFP Universitas Bengkulu, 2024)
[ANALYSIS OF MANGROVE LAND CAPABILITIES IN SURABAYA CITY UTILIZING GEOGRAPHIC INFORMATION SYSTEM]. Mangroves are experiencing rapid growth and require optimal management. Assessing the land potential is crucial for developing necessary policies to evaluate mangrove areas and determine their suitability for mangrove plantations. Findings from land evaluation offer valuable guidance for land use according to specific requirements. Assessing land capacity serves as a reference to determine suitability, with mapping based on mangrove vegetation in the Surabaya region. This research aims to identify and assess the suitability of land along the Surabaya coast for mangrove cultivation. Results indicate that mangroves in Surabaya City fall into ability classes V and VII. Limiting factors include drainage conditions and physical properties such as soil texture, permeability, and salinity. Proper land use is determined based on land capability classes, designating areas as nature reserves and protected forests.